Moyamoya disease in a young woman with intraand extracranial vessels involvement on vessel wall imaging - Toh, Tsun Haw; Tan, Kay Sin; Ramli, Norlisah; Rahmat, Kartini; Tan, Chong Tin; Lau, Kar Foo; Tai, Mei Ling Sharon (ASEAN Neurological Association, 2019)
[No abstract available]